Da sociedade disciplinar à sociedade de controle: interações em sala de aula do ensino médio diferenciação de si no processo de ensino e aprendizagem - Barbosa, Aldovano Dantas [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The research investigated the relationships of power and interaction in the classroom of high school and its implications for learning room analyzing transition called disciplinary society to the society of control, with methodological strategies of ethnographic research in order to consider the theories and pedagogical practices put into action today and its effects of production of subjectivity . Focusing on the issue of disciplinary devices in class room and learning how to differentiate themselves . With a view to these goals observations of 20 teachers were held on schedule ATPC and 80 students in their class in a state secondary school in the west of the city of Franca . Were also analyzed school documents , and observation of other professionals that make up the educational context . The data were subjected to content analysis and subsequently interpreted according to the concepts of Michel Foucault , Gilles Deleuze and Félix Guattari . The analyzes showed that the place teacher / student is well defined within the call control and disciplinary society , and that the lines of hard, rigid interactions and leakage are mixed and composes the existing institutional framework. Therefore , the school institution is as rigid as needed to spread the disciplinary society and the society of control

A pesquisa realizada investigou as relações de poder e interação em sala de aula do Ensino Médio e suas implicações para a aprendizagem analisando a transição da chamada sociedade disciplinar para a sociedade de controle, com estratégias metodológicas da pesquisa etnográfica em vista de considerar as teorias e as práticas pedagógicas colocadas em ação hoje e seus efeitos de produção de subjetividade. Enfocando a questão dos dispositivos disciplinares em sala de aula e a aprendizagem como diferenciação de si. Com vista a estes objetivos foram realizadas observações de 20 professores, em horário de ATPC e 80 alunos, em suas respectivas classes, em uma escola estadual de Ensino Médio na zona oeste da cidade de Franca. Foram também analisados documentos da escola, além da observação de outros profissionais que compõem o contexto educacional. Os dados foram submetidos à análise de conteúdo e, posteriormente, interpretados segundo as concepções de Michel Foucault, Gilles Deleuze e Félix Guattari. As análises demonstraram que o lugar professor/aluno é bem delimitado dentro da chamada sociedade disciplinar e de controle, e que as linhas de interações duras, rígidas e de fuga são mistas e compõe o quadro institucional vigente. Portanto, a instituição escolar é tão rígida quanto necessário para difundir a sociedade disciplinar e a sociedade de controle
Keywords: Serviço social - Estudo e ensino; Analise de interação em educação; Educação - Estudo e ensino - São Paulo (Estado); Ambiente escolar; Ensino médio - Franca (SP); Aprendizagem; Social service